Entrance and run angle variations of hull form preserving the prismatic coefficient - Eun-Young Son; Min-Jae Oh; Se-Jin Oh; Myung-Soo Kim; Yoo-Chul Kim (International Journal of Naval Architecture and Ocean Engineering, 2023)
There are several methods of hull form variation that can be used in initial ship design, such as offset variation, line variation, and hull form variable variation. Hull form variations are typically done manually, and different results can be obtained according to the designer's know-how. This study proposes a conversion method that uses the Free-Form Deformation method to vary the entrance angle and run angle among the variables that are capable of converting hull form. The Free-Form Deformation is a method for transforming shapes. The variation using Free-Form Deformation method has the advantage of allowing for smooth conversion of the overall shape of the object to be varied, so the local variation is smoothly controlled when a designer manually transforms. However, if the Free-Form Deformation method is used, the varied entrance angle and run angle of the bow and stern will be changed, as will the prismatic coefficient, which is a constraint. Therefore, to obtain the same prismatic coefficient from before the variation, a method of correcting the prismatic coefficient converted 1-CP variation while maintaining the entrance angle and run angle was proposed, and the result was verified. The proposed method can shorten the time needed to generate various hull form data to identify the optimal hull form. It will also help strengthen the competitiveness of small and medium-sized shipbuilders who lack hull form variation technology, as they can use the proposed method to obtain an optimal hull form.